Adverse childhood experience and depression: the role of gut microbiota - Bai, Yu; Shu, Chang; Hou, Ying; Wang, Gao-Hua (Frontiers in Psychiatry, 2024)
Depression is the most common psychiatric disorder that burdens modern society heavily. Numerous studies have shown that adverse childhood experiences can increase susceptibility to depression, and depression with adverse childhood experiences has specific clinical-biological features. However, the specific neurobiological mechanismsare not yet precise. Recent studies suggest that the gut microbiota can influence brain function and behavior associated with depression through the "microbe-gut-brain axis" and that the composition and function of the gut microbiota are influenced by early stress. These studies offer a possibility that gut microbiota mediates the relationship between adverse childhood experiences and depression. However, few studies directly link adverse childhood experiences, gut microbiota, and depression. This article reviews recent studies on the relationship among adverse childhood experiences, gut microbiota, and depression, intending to provide insights for new research.